Anti-emetic Effect of Mosapride Citrate Hydrate, a 5-HT4 Receptor Agonist, on Selective Serotonin Reuptake Inhibitors (SSRIs)-Induced Emesis in Experimental Animals - Yukiko Mine; Seiko Oku; Naoyuki Yoshida (Elsevier, 2013)
Although selective serotonin reuptake inhibitors (SSRIs) are widely used to treat depression, they frequently cause gastrointestinal adverse effects, such as nausea and emesis. In the present study, we investigated the anti-emetic effect of mosapride, a 5-HT4 receptor agonist, on SSRIs-induced emesis in Suncus murinus and dogs. We also examined the effect of mosapride on SSRIs-induced delay in gastric emptying and increase in gastric vagal afferent activity in rats. Oral administration of paroxetine, but not its subcutaneous administration, dose-dependently caused emesis in both animals. Mosapride inhibited paroxetine-induced emesis in Suncus murinus and dogs with ID50 values of 7.9 and 1.1 mg/kg, respectively. The anti-emetic effect of mosapride was partially inhibited by SB207266, a selective 5-HT4 antagonist. Intragastric administration of paroxetine increased gastric vagal afferent discharge in anesthetized rats. Mosapride failed to suppress this increase. On the other hands, mosapride improved the delay in gastric emptying caused by paroxetine in rats. We have shown in this study that oral administration of SSRIs causes emesis and activates gastric vagal afferent activity in experimental animals and that mosapride inhibits SSRIs-induced emesis, probably via improvement of SSRIs-induced delay in gastric emptying. These findings highlight the promising potential of mosapride as an anti-emetic agent. Keywords:: mosapride citrate hydrate, 5-HT4 receptor agonist, emesis, anti-emetic effect, selective serotonin reuptake inhibitors (SSRIs)